AB1279 PHYSICAL ACTIVITY LEVELS AND ATTITUDES IN PATIENTS WITH AXIAL AND PERIPHERAL SPONDYLOARTHRITIS. (June 2019) - Liu, Shao-Hsien; Shridharmurthy, Divya; Lapane, Kate; Morais, Stephen; Dubé, Catherine; Kay, Jonathan
Abstract : Background: Spondylarthritis is one of the common inflammatory rheumatic diseases in adults, with an overall prevalence of 0.5 to 1%. Based on clinical manifestations and the Assessment in Spondylarthrosis International Society (ASAS) criteria, spondyloarthritis can be distinguished as predominately axial or peripheral. Despite the health-related benefits of regular physical activity, patients with spondyloarthritis, are generally less active than those without disease. Studies evaluating the differences in physical activity levels and attitudes towards exercise of patients with axial and peripheral spondyloarthritis are limited. Objectives: To characterize and compare self-reported physical activity and attitudes towards exercise among patients with axial and peripheral spondyloarthritis. Methods: We used baseline information from an on-going, longitudinal, single-site, prospective cohort study consisting of 244 patients with spondyloarthritis including psoriatic arthritis, ankylosing spondylitis, and other spondyloarthropathies. Attitudes and beliefs towards exercise were assessed from 5 domains including: 1) general attitude towards exercise; 2) support from other people; 3) benefits in exercise/physically active; 4) concerns about being active; and 5) exercise/physical activity behavior. A continuous scale (range: 0 -100) was used to evaluate attitudes and beliefs towards exercise. High scores indicated that the individual found exercise to be beneficial and/or liked engaging in physical activity. Physical activity was evaluated using the Nurses' Health Study physical activity questionnaire II (NHSPAQ II). Physical activity levels were assessed using the total metabolic equivalent (MET) to incorporate the frequency, duration and intensity by different type of activities. Minutes spent in each level of activity (e.g., sedentary, light, moderate, and vigorous) were then summed for each week. Adjusted multivariable linear models estimated the relationship between physical activity levels and disease status. Results: Overall, nearly 80% of the study sample had predominantly peripheral spondyloarthritis. The average age for participants with peripheral disease was 53.2 (standard deviation (SD):12.9) and for those with axial disease was 44.2 (SD: 12.4). Most of the study participants were men, white, non-Hispanic, married, and had attended at least some college, regardless of predominant joint distribution (peripheral versus axial). While the median for general attitude towards regular exercise in participants with peripheral disease was 88.5, the median score was 81.0 in participants with axial disease. The median score regarding benefits of exercise/physical activity to improve general function was 97.0 among participants with peripheral disease and 95.5 among those with axial disease; the median score for pain relief was 67.0 in participants with peripheral disease and 66.5 for those with axial disease. Regardless of predominant joint distribution, walking, bicycling, and swimming were the most common types of exercise. Compared to participants with predominately peripheral disease, participants with axial disease spent more time per week engaging in light physical activities (adjusted β: 13.0 hrs/week; 95% confidence interval: 0.4 to 25.6 hrs/week) after adjusting for sociodemographic and clinical factors. Conclusion: Patients with spondyloarthritis have positive attitudes towards physical activity/exercise, regardless of their predominant joint distribution, and believe that these activities improve general function and, to a lesser extent, relieve pain. However, patients with axial disease spend more time per week engaging in light physical activities than do those with peripheral disease. Acknowledgement: This work was supported by a generous donation from Timothy S. and Elaine L. Peterson. Disclosure of Interests: Shao-Hsien Liu Grant/research support from: Novartis, Divya Shridharmurthy: None declared, Kate Lapane Grant/research support from: Novartis, Merck, Pfizer, Janssen, Consultant for: Pfizer, Stephen Morais: None declared, Catherine Dubé Grant/research support from: Novartis, Jonathan Kay Grant/research support from: Gilead Sciences, Pfizer, UCB Pharma, Consultant for: AbbVie, Boehringer Ingelheim GmbH, Celltrion Healthcare, Merck Sharp & Dohme Corp., Novartis Pharmaceuticals, Pfizer, Samsung Bioepis, Sandoz, UCB Pharma